SYNAGOGUE: DEFINITION AND HISTORY - Toshpulatov Jasur Djaffarovich; Djuraev Jokhongir Baxodirovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
The synagogue is the central point for life as a Jewish community- it is where many rites of passages take place. It is important as a place of study e.g. it is where a young boy/girl will learn Hebrew and study the Torah in preparation for their bar/bat mitzvahs. They believe that any prayer can only take place where there are at least 10 adults. The synagogue is the central point for life as a Jewish community - it is where many rites of passages take place. This scientific article studied the definition and the history of Synagogue.